Analysis of Women's Protection Law in Divorce Case - Santi; Rusdin Alauddin; Nam Rumkel (LEGAL BRIEF, 2022)
The Supreme Court Regulation Number 3 of 2017 has not been implemented as a whole in divorce cases in the Religious Courts, women who file for divorce (divorce lawsuits) have not fully obtained their rights due to divorce, and divorces that occur in religious courts are mostly divorce lawsuits. The purpose of the study is to find out the extent to which judges apply Supreme Court Regulation Number 3 of 2017 in deciding cases, especially divorce cases against Verstek's decision, and the obstacles faced by judges in implementing Supreme Court regulations Number 3 of 2017. This study uses empirical normative research methods, while data collection techniques are carried out by interviewing, observing and reviewing literature, books and other information relevant to the study. The results of the study show that the Supreme Court Regulation Number 3 of 2017 is very important and very helpful for judges in making decisions but until now Judges are still having difficulty executing Verstek Divorce Decisions if in the decision there are ex-wife rights due to divorce, especially non-civil servants